4p+7=12+3p

Simple and best practice solution for 4p+7=12+3p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4p+7=12+3p equation:


Simplifying
4p + 7 = 12 + 3p

Reorder the terms:
7 + 4p = 12 + 3p

Solving
7 + 4p = 12 + 3p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-3p' to each side of the equation.
7 + 4p + -3p = 12 + 3p + -3p

Combine like terms: 4p + -3p = 1p
7 + 1p = 12 + 3p + -3p

Combine like terms: 3p + -3p = 0
7 + 1p = 12 + 0
7 + 1p = 12

Add '-7' to each side of the equation.
7 + -7 + 1p = 12 + -7

Combine like terms: 7 + -7 = 0
0 + 1p = 12 + -7
1p = 12 + -7

Combine like terms: 12 + -7 = 5
1p = 5

Divide each side by '1'.
p = 5

Simplifying
p = 5

See similar equations:

| 7.6x+3=6.6x | | r=51-2r | | (4x+5)(3y-7)= | | 6(4-3)-5(4+2)=8 | | x^2-5x=2x^2+x | | 6x+3.9=53.1 | | (x^3+11x^2+18x)/(x^2-6x-16) | | .06x+.03(6000-x)=219 | | (9z^2+30z+25)/(9z^2+9z-10) | | (-2/w+4)=(-5/2w+8)+2 | | 4^(3/2) | | (t^2-16)/(t-4) | | Wxy+6=a | | 7x+10+x+20+2x=180 | | -4(x+5)=-16 | | sqrt(3x^2-3)=3 | | 12(t-5)+6t=6(3t+3)-10 | | 1/x=(x/6)-(5/60) | | 8=(-12)+k/(-4) | | sqrt(x^2-25)=4 | | -4=7x+1/(-8) | | (-4k^4+14*3k^2)+(-3k^4-14k^2-8)= | | 8/5x-8=4/3 | | -3x+y=-23 | | y=7/8x+10 | | .16y+.02(y+2000)=1660 | | Y=-16x^2+22x+3 | | 4/(m-8)=8/2 | | F(x)=-16x^2+22x+3 | | (3/X+20)-(4/X-20)=4X/X^2-400 | | 2(6)-3y=9 | | 1/2s+4=6 |

Equations solver categories